ANALISIS DAMPAK PANDEMI COVID 19 TERHADAP PELAKU USAHA PADA OBYEK WISATA MC EDUPARK DI KECAMATAN CEPU KABUPATEN BLORA - Adiseputra, Yudhistira; Artha, Bhenu; Kartika, Fiki (Universitas Islam Lamongan, 2023)
This research was conducted with the aim of finding out how the impact of Covid-19 is on social and economic conditions in business actors around the MC Edupark Tourism Object, Cepu District, Blora Regency. Data were analyzed using interactive qualitative analysis models and purposive sampling to determine informants related to the research object. Data collection techniques in this study are Observation, Interview, Documentation. The data analysis technique used is qualitative, with steps that include: Data collection, data presentation and drawing conclusions and suggestions. The population in this study were 31 traders and 40 tourists in the Mc Edupark tourism area, Blora Regency. The results of the study show that business opportunities around the Mc Edupark tourism object are included in the high category. Local people take advantage of this situation to trade. The increase in visitors after the renovation of the Mc Edupark Tourism Object was really able to increase visitors and affect an increase in income.